2018
DOI: 10.1186/s12916-018-1019-5
|View full text |Cite
|
Sign up to set email alerts
|

The Cambridge Prognostic Groups for improved prediction of disease mortality at diagnosis in primary non-metastatic prostate cancer: a validation study

Abstract: BackgroundThe purpose of this study is to validate a new five-tiered prognostic classification system to better discriminate cancer-specific mortality in men diagnosed with primary non-metastatic prostate cancer.MethodsWe applied a recently described five-strata model, the Cambridge Prognostic Groups (CPGs 1-5), in two international cohorts and tested prognostic performance against the current standard three-strata classification of low-, intermediate- or high-risk disease. Diagnostic clinico-pathological data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 37 publications
1
56
0
1
Order By: Relevance
“…However, guidelines on risk‐based management never only use Grade as a criterion and always use a composite of PSA, Grade, and Stage (AUA, National Comprehensive Cancer Network [NCCN], EAU, NICE). Moreover, we have previously seen in our two reports on the CPG model development and validation that men with GG2 and a high PSA level have similar outcomes to men with GG3 and a low PSA level . For these reasons, we feel that it is the composite score that is most relevant to clinical practice and AS management.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, guidelines on risk‐based management never only use Grade as a criterion and always use a composite of PSA, Grade, and Stage (AUA, National Comprehensive Cancer Network [NCCN], EAU, NICE). Moreover, we have previously seen in our two reports on the CPG model development and validation that men with GG2 and a high PSA level have similar outcomes to men with GG3 and a low PSA level . For these reasons, we feel that it is the composite score that is most relevant to clinical practice and AS management.…”
Section: Discussionmentioning
confidence: 87%
“…Our recent work has explored the innate heterogeneity within the traditional intermediate‐risk classification and shown two distinct sub‐groups with very different mortality and metastatic risks . In the present study, we put this sub‐classification to the test by comparing PCM in men managed by either immediate radical therapy or conservative means.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…the new AUA/American Society for Therapeutic Radiology and Oncology [ASTRO]/Society of Urologic Oncology [SUO] Prostate Cancer Guidelines). Large cohort studies have further confirmed that such sub‐stratification can indeed separate ‘intermediate‐risk’ men into good‐ and poor‐survival groups in terms of cancer mortality . An interesting question then arises as to what then actually constitutes ‘clinically significant’ or lethal disease.…”
mentioning
confidence: 98%
“…Over recent years there has been an increasing awareness that our ideas on the lethality of primary non‐metastatic prostate cancer may need to change. This concept has emerged from a number of different sources including randomised controlled trials, reports from mature active surveillance programmes, and prognostic modelling work in large populations . The evidence suggests that for many men without metastatic disease (85% of all presentations from the recent UK National Prostate Cancer Audit) tumours will evolve slowly and will not translate into cancer‐related mortality, at least, not within the first 10–15 years of its natural history.…”
mentioning
confidence: 99%